Digital Strategic Communication through Social Media: Building Brand Relationships and Customer Loyalty - Yovita Amanda Putri; Febri Nurrahmi (ULTIMA Comm, 2026)
Atariki Japan is a local culinary brand offering ramen and Japanese cuisine with flavors adapted to the preferences of the Acehnese community. Amid increasing culinary competition, Atariki Japan utilizes social media as a strategic communication platform to build relationships with customers and strengthen brand loyalty. This study aims to examine how Atariki Japan implements digital strategic communication through social media, how these strategies contribute to brand–customer relationships, and how these relationships influence customer loyalty. This study employs a qualitative case study approach using Relationship Management Theory. Data were collected through semi-structured interviews with five informants, consisting of Atariki Japan’s chief marketing officer, content creator, and three customers, supported by social media documentation analysis. The findings reveal that Atariki Japan implements digital strategic communication through four strategies: content creation, content sharing, connecting, and community building. These strategies enable Atariki to establish interactive communication, develop emotional connections, and foster a sense of belonging among customers. Furthermore, brand relationships developed through social media contribute to customer loyalty, reflected in customer trust, emotional attachment, continued preference, repeat visits, and recommendations to others. This study concludes that social media functions as a strategic platform for managing sustainable brand–customer relationships.